Assessment and Interpretation of Attacking Actions in Volleyball - Kazakhov Bakhramjon; Allayarov Dilshod (Zien Journals, 2022)
The work experience of specialists on the issue of assessing technical and tactical skills in volleyball is summarized. The effectiveness of competitive activity is determined by individual indicators of technical and tactical activity of players, which bring effective actions of a team or an individual player. As a result of a theoretical analysis of the assessment of technical and tactical actions in volleyball, the coefficient of effectiveness of attacking actions was determined
Keywords: components of technical and tactical activity; qualified volleyball players; evaluation of technical and tactical skills